Pushing the limit of liver regeneration – Safety and survival after monosegment-ALPPS: systematic review and individual patient data meta-analysis. Issue 3 (March 2022) - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Schulz, Erik; Sterkenburg, Anthe; Probst, Pascal; Hoffmann, Katrin
Abstract: Background: Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has expanded and spearheaded development in hepatobiliary surgery. Monosegment-ALPPS tests liver regeneration limits and may present as the last feasible curative treatment option. Methods: Electronic databases (MEDLINE, Web of Science, Google Scholar, Cochrane Library and WHO International Clinical Trials Registry Platform) were searched for publications on mono-ALPPS using a predefined strategy without date or language restrictions. Individual patient data was extracted and analyzed. Results: 237 publications were identified. 19 patients were identified to have undergone mono-ALPPS. Primarily, mono-ALPPS has been utilized as curative treatment for CRLM (17 of 19 cases). Successful mono-ALPPS was possible in FLR above 8% SLV. All patients received either chemotherapy alone or in combination with radiotherapy prior to surgery. 8 of 19 patients experienced PHLF grade A or B. There was no in-hospital mortality described. Recurrent disease has occurred in 7 of 19 patients and 3 have died during follow-up. Conclusion: Mono-ALPPS is an experimental procedure that provides a reasonably safe opportunity to curatively treat extensive liver malignancies in patients with FLR as low as 8% SLV. PHLF is the most prevalent complication in mono-ALPPS. Mono-ALPPS should be evaluated in a multicentral study setting.